Interpersonal Perceptions of Adverse Peer Experiences in First-Grade Students - García Bacete, Francisco J.; Sureda-García, Inmaculada; Muñoz-Tinoco, Victoria; Jiménez-Lagares, Irene; Marande Perrin, Ghislaine; Rosel, Jesús F. (Frontiers in Psychology, 2018)
Objective: The aim of this study was to identify which adverse peer experiences better predict perceived negative peer relationships among elementary school first graders according to sex. The peer experiences examined were peer rejection, peer victimization, and mutual antipathy; the interpersonal perceptions studied were perceived peer victimization, dyadic meta-perception of peer disliking, and loneliness. Method: The participants were 809 children (Mage = 6.4 years, SD = 0.32; ngirls= 412, 50.9%) enrolled in 35 first-grade classes from 15 schools in 4 Spanish regions: Valencia, n= 276, 34.1%; Balearic Islands, n= 140, 17.3%; Andalusia, n= 199, 24.6%; Castile-Leon, n= 194, 24%. We calculated sex differences in peer experiences and interpersonal perceptions by means of one-way ANOVA for means differences and Fisher's r-to-z transformation for correlations differences. We used a multilevel regression analysis (nesting variables: class and region) to determine whether the associations between each peer experiences and each perception were unique. Results: Each adverse peer relationship predicted each interpersonal perception differentially. Peer victimization was a good predictor of the three interpersonal perceptions, and the only predictor of perceived peer victimization. Peer rejection predicted loneliness, whereas mutual antipathies predicted dyadic meta-perception of peer disliking, although more so among girls. A significant effect at region level was found but not at class level. Conclusion: Our findings suggest that research should take into account the different levels of the social peer system when analyzing peer experiences within the classroom context. The study contributes to sensitize teachers about the greater responsiveness of 6-year old girls to adverse peer experiences, and it could be useful for designing interventions that would help children oppose rejection and empower active bystanders to fight against peer mistreatment.